Molecular Links Between Circadian Rhythm Disruption, Melatonin, and Neurodegenerative Diseases: An Updated Review - Kemal Hüsnü Can Baser; Ismail Celil Haskologlu; Emine Erdag (Molecules)
Circadian rhythms are molecular oscillations governed by transcriptional–translational feedback loops (TTFLs) operating in nearly all cell types and are fundamental to physiological homeostasis. Key circadian regulators, such as circadian locomotor output cycles kaput (CLOCK), brain and muscle ARNT-like 1 (BMAL1), period (PER), and cryptochrome (CRY) gene families, regulate intracellular metabolism, oxidative balance, mitochondrial function, and synaptic plasticity. Circadian disruption is known as a central contributor to the molecular pathophysiology of neurodegenerative disorders. Disease-specific disruptions in clock gene expression and melatoninergic signaling are known as potential early-stage molecular biomarkers. Melatonin, a neurohormone secreted by the pineal gland, modulates clock gene expression, mitochondrial stability, and inflammatory responses. It also regulates epigenetic and metabolic processes through nuclear receptors and metabolic regulators involved in circadian and cellular stress pathways, thereby exerting neuroprotective effects and maintaining neuronal integrity. This review provides recent findings from the past five years, highlighting how circadian dysregulation mediates key molecular and cellular disturbances and the translational potential of circadian-based therapies in neurodegenerative diseases.